CCN5 Drives Leydig Cell Aging and Testicular Dysfunction: Insights into Fibrosis, Lipid Dysregulation, and Therapeutic Potential - Xiaoli Tan; Yanghua Xu; Ningjing Ou; Yuzhuo Chen; Wanyi Xia; Emily Xing; Ren Mo; Hao Bo; Zhitao Han; Jiarong Xu; Zepeng Dong; Yingbo Dai; et al. (Research, 2025)
Leydig cells’ (LCs’) senescence is an important reason for the decline of testicular function in elderly men. Cellular communication network factor 5 (CCN5) regulates lipid metabolism and cellular fibrosis through multiple mechanisms. However, its role in LCs’ aging and the underlying molecular mechanisms remain unclear. This study aimed to elucidate the effects and molecular mechanisms by which CCN5 drives aging phenotypes in LCs and to evaluate the potential of targeting CCN5 as a therapeutic strategy for testicular aging. CCN5 expression was located in LCs and elevated in aged testis. Overexpression of CCN5 led to LCs’ aging and testis dysfunction. Extracellularly, CCN5 activated β-catenin and SMAD2/3 phosphorylation, promoting the expression of fibrosis-related genes. Intracellularly, CCN5 did not affect de novo cholesterol synthesis-related genes but changed the balance of cholesterol transporters. CCN5 bound to and reduced ring finger protein 213 (RNF213) protein levels. RNF213 knockdown activated forkhead box O, p16, and p21, resulting in SA-β-gal activation, reduced cell proliferation, and lipid droplet loss. In aged mice, CCN5 knockdown improved testicular atrophy, restored lipid droplet content and testosterone synthesis, and enhanced physical endurance and sexual behavior. In summary, CCN5 drives LCs’ aging and testicular dysfunction maybe via promoting fibrosis and lipid droplet loss. Targeting CCN5 offers a promising strategy to treat testicular aging and associated reproductive endocrine disorders.